2005
DOI: 10.1065/espr2005.08.275
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Lead in Urban Soils from Selected Cities in a Central Region of the Philippines (7 pp)

Abstract: The findings of this study presented a preliminary survey on the extent of Pb contamination of soils in urban cities in central region of Philippines Island. With this kind of information on hand, government should develop a comprehensive environmental management strategy to address vehicular air pollution in urban areas, which shows as one of the most pressing environmental problems in the country. Basic to this is the continuous monitoring of Pb levels and other pollutants in air, soil, and water. Further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 3 publications
1
24
0
2
Order By: Relevance
“…Diesel exhaust is believed to consist of thousands of organic constituents and is a major cause of urban pollution (Bayona et al 1988;Draper 1986;Erdinger et al 2005;Mestres 2005;Morville 2006;Ona 2006;Schuetzle 1983;Schuetzle & Lewtas 1986;Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel exhaust is believed to consist of thousands of organic constituents and is a major cause of urban pollution (Bayona et al 1988;Draper 1986;Erdinger et al 2005;Mestres 2005;Morville 2006;Ona 2006;Schuetzle 1983;Schuetzle & Lewtas 1986;Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Shooting activities have been reported to be the largest contributors of lead to the environment (USGS, 2002).The most commonly applied pozzolanic materials are portland cement, lime, and/or fly ash (Palomo and Palacios, 2003;Dermatas and Meng, 2003;and Terzano et al, 2005).The lead in fuels contributes to air pollution, especially in urban areas. Soil near highways, freeways, and smelting facilities have higher levels of lead than the soil in other areas because of their exposure to lead dust, which accumulates over time (Ona et al, 2006).The impact of mineral extraction occurs not only in the mine zone, but also in the surrounding areas when polluted sediments are carried out by rivers and runoff (Jiménez-Cárceles et al, 2008).…”
Section: Types Of Heavy Metals Contamination In Soilmentioning
confidence: 99%
“…The process of urbanization and industrialization is accompanied by increased automobile and industrial emissions of heavy metals to surrounding water bodies (Arnason and Fletcher, 2003;Vaalgamaa, 2004). Except industrial emission, most heavy metals have significant traffic related sources (Callender and vanMetre, 1997;Gardner and Carey, 2004;Ona et al, 2006). Even treated urban effluents can serve as point sources of metal contaminants to receiving waters (Gobeil et al, 2005), and it has been shown that management of storm water in urban areas leads to the accumulation of polluted sediments at the water-sediment interface of various aquatic ecosystems (Mermillod-Blondin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%